2020
DOI: 10.1128/jcm.01828-20
|View full text |Cite
|
Sign up to set email alerts
|

Global Molecular Epidemiology of Respiratory Syncytial Virus from the 2017−2018 INFORM-RSV Study

Abstract: Respiratory syncytial virus (RSV) is the leading cause of lower respiratory tract infection among infants and young children, resulting in annual epidemics worldwide. INFORM-RSV is a multi-year clinical study designed to describe the global molecular epidemiology of RSV in children under five years of age by monitoring temporal and geographical evolution of current circulating RSV strains, F protein antigenic sites, and their relationships with clinical features of RSV disease. During the pilot season (2017–20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
72
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 42 publications
6
72
0
3
Order By: Relevance
“…Several other minor variants were also identified in the antigenic sites of the F protein. None of these variants have been reported before except for S255N 25 , whose susceptibility to monoclonal antibodies has not been examined. Stochastic (random) patterns were found in the temporal changes of within-host virus diversity and minor variants.…”
Section: Discussionmentioning
confidence: 99%
“…Several other minor variants were also identified in the antigenic sites of the F protein. None of these variants have been reported before except for S255N 25 , whose susceptibility to monoclonal antibodies has not been examined. Stochastic (random) patterns were found in the temporal changes of within-host virus diversity and minor variants.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence studies replaced mAb reactivity to identify strain differences and found both in subsequent studies of RSV transmission in healthcare settings [ 52 , 53 ]. G gene sequence studies have also helped understand community RSV outbreaks and shown the co-circulation of multiple genotypes in one season in a community, different patterns of genotypes in nearby communities during the same season, and clarified household transmission [ 17 , 18 , 54 , 55 , 56 ]. One conclusion from these studies is that yearly community RSV outbreak strains are not dominated by regional or national strains.…”
Section: Structure Of Gmentioning
confidence: 99%
“…In this strain, aa 261–283 are duplicated and inserted between aa 284 and 285, which results in a 23 aa longer G protein. Viruses with the G duplication, both Subgroup A and B, have spread globally, and variants of the original viruses have become the dominant currently circulating strains [ 55 , 66 , 67 ]. In vitro studies on reverse genetics-derived Subgroup B viruses with and without the G duplication showed that, the duplication likely improved virus attachment in binding to heparin sulfate proteoglycans on the cell surface and conferred a competitive replication advantage [ 68 ].…”
Section: Structure Of Gmentioning
confidence: 99%
“…Molecular surveillance of the 2017–2018 F sequences from eight countries showed high-frequency polymorphisms at antigenic sites Ø and V of RSV B that included 100% detection of the nonconservative polymorphisms in suptavumab target site V (L172Q/S173L). Conservative polymorphisms in nirsevimab target site Ø (I206M/Q209R) [ 54 ] were detected in 77% of RSV B strains, but they retained susceptibility to neutralization by nirsevimab [ 55 ].…”
Section: Challenges and Opportunities In Bringing Rsv Monoclonal Antibody To Lmicsmentioning
confidence: 99%